Interventionist industry policy to support local value-adding: Evidence from the Eastern Indonesian seaweed industry. (May 2023) - Langford, Alexandra; Turupadang, Welem; Waldron, Scott
Abstract: Indonesia has long considered the use of trade restrictions to encourage the development of domestic value-adding in primary production. In 2015, these were suggested as a strategy to support the development of a national seaweed processing industry, however, such policies were ultimately not implemented on a national level. In August 2022, the eastern Indonesian province of Nusa Tenggara Timor implemented a ban on trade of raw seaweed outside of the province, aiming to increase supply of seaweed to local processors and encourage further investment in local processing capacity, with the ultimate goal of supporting increased value-adding and the development of the local seaweed processing sector. The policy was accompanied by establishment of government mandated price floors for the three seaweed processors located in the province. This article examines the execution and potential implications of this new policy with several findings. First, there is a lack of clarity in the definition of 'value-adding' and the types of processing developments that the regulation seeks to incentivise. Second, the province does not consistently have the capacity to process all of the seaweed it produces, exacerbating the negative impacts of trade restrictions on farmers. Third, the purpose of the price floor and its relationship to market prices in other regions is unclear and prevents differentiation by product quality, reducing incentives for farmers to increase production quantities and qualities. Fourth, the province is experiencing difficulty enforcing the seaweed export restrictions such that the ban has incentivized an increase in unofficial seaweed trade out of the province. The article recommends the regulation be revised or revoked and other strategies to support value adding in the region be considered.